(untitled) (Journal of Parents and Teachers, 2026)
If, at birth, our children were aware of how inexperienced we are, they would surely exclaim: Help, I’m going back to where I was! Many times I have had, and still have, the feeling that my children have been guinea pigs or test subjects. As parents, we learn as we go along with them. By spending a lot of time with them, I learned how they learned, and that no one better than them could tell me what was best for them. Children are the best teachers.